Некоторые структурные особенности именных словосочетаний в современном русском языке - Жарких, И. (Kalbotyra, 1972)
The above analysed material gives us an opportunity to make the following conclusion.From our point of view, the structure of the noun constructions in colloquial speech depends on the type of communication: on its being a dialogue, on emotionality, on spontaneity.It must be also added that the active processes of modem syntax are particularly reflected in the structure or noun constructions.It seems that a detailed structure analysis of the noun constructions will be very useful for a Practical Course of the Russian Language.